Preslaughter transportation and shower management on broiler chicken Dead on Arrival (DOA) incidence - Oliveira Silva, Janaina Aparecida Aparecida (2011)
The aim of this work was to evaluate the influence of the management conditions and distance to a commercial plant on chicken broilers Dead on Arrival (DOA). This work was conducted in the winter and summer seasons of 2008 in a commercial plant. In the winter season, the transport distances were 15 and 57 km, and in the summer season the distances were 15 and 55 km from the farm to the slaughterhouse and the experiments were carried out in duplicate. In the summer, to evaluate the effect of water bath over the birds before the actual transportation, a group of two trucks were submitted to a water bath (GWthB) and the other without water bath treatment (GWoutB). The results showed that in the winter, the DOA was not influenced to distance of transport. In the summer, the DOA values for GWthB group varied from 0.12 to 0.17% while for the GWoutB the DOA values ranged from 0.16 to 0.27% indicating that the bath treatment after broilers truck loading and before transportation reduced broiler chicken mortality.